Peer conferencing and teacher-student conferencing as alternative or combination revision strategies / Jayakaran Mukundan, Lor Siew Chu and Anealka Aziz Hussin - Mukundan, Jayakaran; Lor, Siew Chu; Aziz Hussin, Anealka (UPENA, 2006)
It is a fallacy to assume that Form Five students in Malaysian schools have already mastered composition-writing strategies. Classroom teaching reveals that they still need to be assisted through effective strategies in composition writing in preparation for the SPM Examination Teachers therefore need to identify an appropriate strategy to assist them in essay writing. The strategies suggested are peer conferencing (Strategy 1) and teacher-student conferencing (Strategy 2) as revision strategies. The objectives of this study are to find out whether these revision strategies are able to improve their writing and to investigate which revision strategy can better assist students in composition writing. Results of the study showed that all students managed to get higher scores regardless of the strategy used. However, students that used Revision Strategy 2 achieved better scores than students that used Revision Strategy 1. It is suggested that teachers should use the strategies either in isolation or integrate both revision strategies in the teaching of writing composition. This is also the view of Campbell (1998) who says that peer and teacher feedback complement each other.